RASIO NEUTROFIL LIMFOSIT SEBAGAI PREDIKTOR LUARAN KASUS CEDERA KEPALA SEDANG DAN BERAT: STUDI MULTISENTER - Hanif Gordang Tobing; Yovanka Naryai Manuhutu; Syaiful Ichwan; Renindra Ananda Aman; Setyo Widi Nugroho; Samsul Ashari; David Tandian; Mohammad Saekhu; Wismaji Sadewo; Affan Priyambodo; Kevin Gunawan; Ande Fachniadin (PERDOSNI, 2021)
Introduction: Traumatic brain injury (TBI) is the most common cause of death in populations less than 40 years old in developed and developing countries. The clinical outcome after TBI is still an issue and difficult to predict. Besides Glasgow Coma Scale (GCS), neutrophil to lymphocyte ratio (NLR) as one of the neuroinflammation biomarkers also can predict outcomes after TBI Aim: To measure the association between NLR and GCS as predictors of moderate and severe TBI outcomes. Methods: This prospective study included moderate and severe TBI patients who underwent craniotomy in a multicenter hospital from November 2019 to November 2020. Chi-square analytic test was used to determine the relationship between demographics, clinical symptoms, NLR and GCS as predictors outcome of moderate and severe TBI. Results: About 54 patients with moderate and severe TBI consist of 41 (75.9%) male and 13 (24.1%) female patients, mean age 27.6 ± 15.3 years, preoperative GCS is 13 (7 - 13), with asymmetric pupil 33 (61.1%), seizures 5 (9.3%), hemiparesis 1 (1.86%), and GCS postoperative on the fifth and seventh day is 14 (6 - 15). Preoperative NLR was 7.4 (1.9-26.2), the cut-off for NLR as a predictor for improved GCS was at 9.8 with a specificity and sensitivity of 87%. Discussion: Low NLR had an association with the patient’s improved GCS, while a high NLR had an association with a non-improving GCS, so that the relationship between RNL and GCS could be used as an outcome predictor of moderate and severe traumatic brain injury patient. Keywords: glasgow coma scale, neutrophil to lymphocyte ratio, predictor, traumatic brain injury